Perancangan Gearbox Turbin Angin Savonius Tipe-L Untuk Pembangkit Listrik Pada Rumah Tinggal - Lidya Daingah; Stenly Tangkuman; Charles Punuhsingon (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2022)
The L-type of Savonius wind turbine is one type of vertical axis wind turbine. The L-type of Savonius wind turbines have proven be an effective wind turbine for converting wind energy into electrical energy. One part that plays a role in the process of converting wind energy to electricity is a gearbox. The gearbox serves to increase the rotation coming from the turbine and then forward it to the alternator. In this research, a gearbox for wind power generation with the L-type of Savonius wind turbine has been designed. The gearbox consists of a pair of gears, two shafts, four bearings, and two keys. The calculation results show that the gearbox speed ratio is 5.3, while the torque on the first shaft is 10.12 Nm and on the second shaft is 1.88 Nm. The stress simulation shows that the von mises stress is less than the allowable stress of the material. Keywords: Gearbox, Savonius Wind Turbine, Speed Ratio